Attitude determination of LEO satellites using an array of GNSS sensors - Nandakumaran, Nadarajah; Teunissen, Peter; Buist, P. (International Society on Information Fusion, 2012)
The proliferation of Global Navigation Satellite Systems (GNSS) paves the way for an increasing number of applications in positioning, guidance and navigation. GNSS based attitude determination is one of such an important and promising application. In this contribution we explore the potential of GNSS-based attitude determination for Low Earth orbiting (LEO) formation flying Synthetic Aperture Radar (SAR) satellites. Precise attitude determination using multiple GNSS receivers/antennas relies on a successful resolution of the integer carrier phase ambiguities. For a set of rigidly satellite-mounted GNSS antennas, a number of nonlinear geometrical constraints can be exploited for the purpose of increasing the probability of correct integer ambiguity estimation. In this contribution, we make use of the Multivariate Constrained Least-squares AMBiguity Decorrelation Adjustment (MC-LAMBDA) method. By incorporating the known antenna geometry into its ambiguity objective function, this method is shown to demonstrate reliable and instantaneous single-frequency integer ambiguity resolution. The resulting attitude estimates are further improved using nonlinear filtering. Our hardware-in-the-loop experiment with the University of New South Wales “Namuru” GNSS receivers shows the potential of stand-alone, unaided, single-frequency attitude determination of LEO satellites.